Perceiving and Acting in the Real World: From Neural Activity to Behavior - Simona Monaco (Frontiers Research Topics, 2016)
One remarkable ability of the human brain is to process large amounts of information about our surroundings to allow us to interact effectively with them. In everyday life, the most common way to interact with objects is by reaching, grasping, lifting and manipulating them. Although these may sound like simple tasks, the perceptual properties of the target object, such as its location, size, shape, and orientation all need to be processed in order to set the movement parameters that allow an accurate reach-to-grasp-to lift movement. Several brain areas work in concert to process this outstanding amount of visual information and drive the execution of a motor plan in just a few hundred milliseconds. How are these processes orchestrated? In developing this type of comprehensive knowledge about the interactions between objects perception and goal-directed actions, we have a window into the mechanisms underlying the functioning of the visuo-motor system. With this research topic we aim to further understand the neural mechanisms that mediate our interactions with the world. Therefore, we particularly encourage submission of papers that attempt to relate such findings to real-world situations by investigating behavioural and neural correlates of information processing related to eye-hand coordination and visually-guided actions, including reaching, grasping, and lifting movements. This topic welcomes submissions of original research using any relevant techniques and methods, from behavioural kinematics/kinetics, to neuroimaging and transcranial magnetic stimulation (TMS), as well as neuropsychological studies.One remarkable ability of the human brain is to process large amounts of information about our surroundings to allow us to interact effectively with them. In everyday life, the most common way to interact with objects is by reaching, grasping, lifting and manipulating them. Although these may sound like simple tasks, the perceptual properties of the target object, such as its location, size, shape, and orientation all need to be processed in order to set the movement parameters that allow an accurate reach-to-grasp-to lift movement. Several brain areas work in concert to process this outstanding amount of visual information and drive the execution of a motor plan in just a few hundred milliseconds. How are these processes orchestrated? In developing this type of comprehensive knowledge about the interactions between objects perception and goal-directed actions, we have a window into the mechanisms underlying the functioning of the visuo-motor system. With this research topic we aim to further understand the neural mechanisms that mediate our interactions with the world. Therefore, we particularly encourage submission of papers that attempt to relate such findings to real-world situations by investigating behavioural and neural correlates of information processing related to eye-hand coordination and visually-guided actions, including reaching, grasping, and lifting movements. This topic welcomes submissions of original research using any relevant techniques and methods, from behavioural kinematics/kinetics, to neuroimaging and transcranial magnetic stimulation (TMS), as well as neuropsychological studies.